Možnost interpretacije frazemov v dvojezičnih slovarjih - Pesehonova Kosem, Liudmila (Slavistična revija, 2016)
Based on examples from Russian-Slovene and Slovene-Russian dictionaries, the author discusses the problem of interpretation of the source-language phrasemes, especially when a translation equivalent in the target language is impoverished, i.e., rendered with a single word. The author presents semantic relationships between a phraseme and its one-word synonym and provides evidence for the inadequacy of a one-word equivalent for a phraseme.
Keywords: bilingual dictionaries; dvojezična leksikografija; dvojezični slovarji; enakovrednost; equivalence; leksikografija; lexicography; prevajanje; Russian; Russian language; ruščina; Slovene; Slovenian language; slovenščina; translation; translational equivalent